Preparation method and application of hollow urchin-shaped 1D / 3D NiCuCo heterostructure nano material

The preparation of hollow sea urchin-shaped 1D/3D NiCuCo heterostructure nanomaterials through hydrothermal synthesis has solved many problems faced by PMS oxidation technology when degrading pollutants in water, and achieved efficient degradation of a variety of organic pollutants, with good economic and environmental benefits.

CN119838600AActive Publication Date: 2025-04-18FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510266498.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-18
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

When degrading pollutants in water, PMS oxidation technology faces problems such as disputes about the types of active oxidants, the impact of pH values, the complexity of pollutants in actual water bodies, the formation and action of singlet oxygen, catalyst cycle stability, and the optimization of PMS concentration.

Method used

Hydrothermal synthesis method is used to combine three metals Ni, Cu and Co under the action of urea to form hollow sea urchin-shaped 1D/3D NiCuCo heterostructure nanomaterial. This material has a good ability to degrade pollutants in water through a simple preparation process.

Benefits of technology

It has achieved the second-level degradation of various organic pollutants, and has efficient pollutant degradation capabilities. It has simple preparation method and low cost, with good economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838600A_ABST
    Figure CN119838600A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a hollow urchin-shaped 1D / 3D NiCuCo heterostructure nano material. According to the preparation method, Ni, Cu and Co are combined together under the action of urea through a simple hydrothermal method, and then centrifugation, washing and freeze-drying are conducted to prepare the hollow urchin-shaped 1D / 3D NiCuCo heterostructure nanometer material. The hollow urchin-shaped 1D / 3D NiCuCo heterostructure nano material prepared by the method has more active sites, can promote PMS to generate more free radicals and efficiently degrade pollutants in water, can degrade about 95% of pollutants within 5 minutes, and has good stability. The preparation method has the characteristics of high economic benefit and simple preparation process, and has good economic benefit and environmental benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology, and specifically relates to a preparation method and application of a hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial. Background Art

[0002] PMS oxidation technology (i.e., peroxymonosulfate system) is an advanced oxidation technology used to degrade pollutants in water. This technology uses persulfate (PMS, usually peroxymonosulfate, Oxone, or sodium persulfate, potassium persulfate, etc.) as an oxidant to produce highly active sulfate radicals (SO4•⁻) under appropriate conditions. These radicals can non-selectively oxidize and mineralize organic pollutants in water. The main bottlenecks faced by the PMS system in degrading pollutants in water include disputes over the types of active oxidants, the influence of pH value, the complexity of pollutants in actual water bodies, the formation and action of singlet oxygen, catalyst cycle stability, and optimization of PMS concentration.

[0003] Therefore, it is necessary to find a material that can be stably applied to the PMS system. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a synthetic hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial. The present invention utilizes a simple hydrothermal synthesis method to combine three metals, Ni, Cu, and Co, together under the action of urea, and then centrifuges, washes, and freeze-dries to form a hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial. The present invention provides a green synthesis method for preparing a hollow sea urchin-shaped 1D / 3DNiCuCo heterostructure nanomaterial that is simple to prepare, has strong versatility and applicability, and the prepared hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial can effectively degrade pollutants in water, the method is simple, the cost is low, and it has good economic and environmental benefits.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial comprises the following steps: (1) dissolving a divalent nickel salt, a divalent copper salt, a divalent cobalt salt and urea in ultrapure water to obtain a mixed solution, and uniformly dispersing the solution by ultrasonication; (2) The mixed solution obtained in step (1) was transferred to a polytetrafluoroethylene reactor and placed in an oven for hydrothermal reaction; (3) The solution obtained in step (2) is centrifuged and freeze-dried to obtain a hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial.

[0006] Furthermore, in step (1), the divalent nickel salt is nickel chloride hexahydrate, the divalent copper salt is copper chloride dihydrate, and the divalent cobalt salt is cobalt chloride hexahydrate.

[0007] Furthermore, the molar ratio of the divalent nickel salt, divalent copper salt, divalent cobalt salt and urea in step (1) is 8.5 mmol: 1 mmol: 1.5 mmol: 60 mmol; and the volume of ultrapure water is 50 mL.

[0008] Furthermore, the ultrasonication time in step (1) is 15 minutes.

[0009] Furthermore, the temperature of the hydrothermal reaction in step (2) is 120° C., and the time of the hydrothermal reaction is 24 hours.

[0010] Furthermore, the centrifugal speed in step (3) is 8000 rpm, the centrifugal time is 3 min, and the centrifugation is performed twice alternately with ethanol and deionized water.

[0011] Furthermore, the freeze-drying step in step (3) is to place the product in a vacuum freeze dryer for 12 hours.

[0012] A hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial prepared by the above method and its application in efficient water treatment.

[0013] The beneficial effects of the present invention are: (1) The present invention adopts a simple hydrothermal synthesis method to combine three metals, Ni, Cu and Co, under the action of urea, and then centrifuge, wash and freeze-dry to form a hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial. A new method for synthesizing a hollow sea urchin-shaped catalyst is provided, which provides a new idea for the preparation of catalysts for efficient degradation of pollutants in water.

[0014] (2) The hollow sea urchin-like 1D / 3D NiCuCo nanomaterial prepared by the present invention is a hollow sea urchin-like structure formed by the combination of needle-like and hollow spheres, and the size of a single particle is about 4 μm.

[0015] (3) Compared with the same type of (hollow sea urchin) materials, the hollow sea urchin-shaped 1D / 3D NiCuCo nanomaterials prepared by the present invention are more porous and have more active sites, and can degrade a variety of organic pollutants in seconds.

[0016] (4) The raw materials and equipment required for the preparation method of the present invention are simple and easy to obtain, the process is simple, easy to operate and safe, and the cost is relatively low; compared with the products prepared by other traditional methods, it has a high efficiency in pollutant degradation ability and is an environmentally friendly new material with good promotion and application value and use prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope (SEM) image of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention.

[0018] Figure 2 This is a scanning electron microscope (SEM) image of the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1 of the present invention.

[0019] Figure 3 This is a scanning electron microscope (SEM) image of the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2 of the present invention.

[0020] Figure 4 This is a transmission electron microscope (TEM) image of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention.

[0021] Figure 5 It is the X-ray diffraction (XRD) diagram of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the thorny ball-shaped NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen from the diagram that the Co element is successfully doped into the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial.

[0022] Figure 6 It is a schematic diagram of the enrofloxacin degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2.

[0023] Figure 7 It is a schematic diagram of the ciprofloxacin degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2.

[0024] Figure 8 It is a schematic diagram of the tetracycline degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2.

[0025] Fig. 9 This is a schematic diagram of the cyclic degradation rate of enrofloxacin in the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention.

[0026] Fig.10 These are the N2 adsorption-desorption curves of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the thorny ball-shaped NiCo heterostructure nanomaterial prepared in Comparative Example 2.

[0027] Fig.11 These are the oxygen vacancy curves of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the thorny ball-shaped NiCo heterostructure nanomaterial prepared in Comparative Example 2.

[0028] Fig.12 Schematic diagram of the degradation rate of enrofloxacin by the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterials prepared in Example 1 of the present invention and nanomaterials synthesized from other transition metals. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings, i.e., embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Example 1 Preparation of hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterials: (1) Weigh 4.25 mmol of nickel chloride hexahydrate, 0.5 mmol of cupric chloride dihydrate, 0.75 mmol of cobalt chloride hexahydrate, and 30 mmol of urea and dissolve them in a beaker containing 50 ml of ultrapure water; (2) Place the beaker in an ultrasonic machine and sonicate for 15 min, then transfer the solution to a 100 ml polytetrafluoroethylene reactor; (3) placing the reactor in an oven at 120°C for 24 hours to perform a hydrothermal reaction; (4) The hydrothermal solution was centrifuged twice with ethanol and deionized water at 8000 rpm for 3 min, and then placed in a vacuum freeze dryer for 12 h to obtain a hollow sea urchin-like 1D / 3D NiCu heterostructure nanomaterial.

[0031] Figure 1This is a scanning electron microscope (SEM) image of the hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention. It can be seen from the image that the hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial is a hollow sea urchin-like structure formed by the combination of needles and hollow spheres, and the size of a single particle is about 4μm. Figure 4 This is a transmission electron microscope (TEM) image of a hollow sea urchin-like 1D / 3DNiCuCo heterostructure nanomaterial. From the image, it can be seen that the hollow sea urchin-like 1D / 3DNiCuCo heterostructure nanomaterial is a hollow sea urchin-like structure formed by the combination of needles and hollow spheres, and the size of a single particle is about 4μm.

[0032] Comparative Example 1 Preparation of hollow sea urchin-like 1D / 3D NiCu heterostructure nanomaterials: (1) Weigh 5 mmol nickel chloride hexahydrate, 0.5 mmol copper chloride dihydrate, and 30 mM urea and dissolve them in a beaker containing 50 ml ultrapure water; (2) Place the beaker in an ultrasonic machine and ultrasonicate for 15 min. Then transfer the solution to a 100 ml polytetrafluoroethylene reactor. (3) placing the reactor in an oven at 120°C for 24 hours to carry out a hydrothermal reaction; (4) The hydrothermal solution was centrifuged twice with ethanol and deionized water at 8000 rpm for 3 min, and then placed in a vacuum freeze dryer for 12 h to obtain a hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial.

[0033] Figure 2 This is a scanning electron microscope (SEM) image of the hollow sea urchin-like 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1 of the present invention. It can be seen from the image that the hollow sea urchin-like 1D / 3D NiCu heterostructure nanomaterial is a hollow sea urchin-like structure formed by the combination of needles and hollow spheres, and the size of a single particle is about 4μm.

[0034] Comparative Example 2 Preparation of spherical NiCo heterostructure nanomaterials: (1) Weigh 5 mmol of nickel chloride hexahydrate, 0.5 mmol of cobalt chloride hexahydrate, and 30 mM of urea and dissolve them in a beaker containing 50 ml of ultrapure water; (2) Place the beaker in an ultrasonic machine and ultrasonicate for 15 min. Then transfer the solution to a 100 ml polytetrafluoroethylene reactor. (3) placing the reactor in an oven at 120°C for 24 hours to carry out a hydrothermal reaction; (4) The hydrothermal solution was centrifuged twice with ethanol and deionized water at 8000 rpm for 3 min, and then placed in a vacuum freeze dryer for 12 h to obtain spherical NiCo heterostructure nanomaterials.

[0035] Figure 3 This is a scanning electron microscope (SEM) image of the thorny spherical NiCo heterostructure nanomaterial prepared in comparative example 2 of the present invention. From the image, it can be seen that the thorny spherical NiCo heterostructure nanomaterial is a thorny spherical structure formed by the combination of needles and solid spheres, and the size of a single particle is about 1.5μm.

[0036] Comparative Example 3 The difference of Example 1 of this comparative example is only that the cobalt chloride hexahydrate is replaced by anhydrous zinc chloride.

[0037] Comparative Example 4 The difference of Example 1 of this comparative example is only that cobalt chloride hexahydrate is replaced by manganese chloride tetrahydrate.

[0038] Application Example 1 Water Pollutant Degradation Experiment The hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial obtained in Example 1 is used to degrade water pollutants, and the specific steps are as follows: (1) Weigh 4 mg of hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterials into a 100 ml beaker, and then measure 40 ml of 10 ppm enrofloxacin solution and add it into the beaker; (2) Ultrasonicate the mixed solution in an ultrasonic machine for 10 seconds. Add a stirring bar to the beaker and place it on a magnetic stirring table. Use a pipette to add 80 μl of the prepared 1 mol / L PMS aqueous solution and start timing. (3) From the start of the timing, draw the solution in the beaker with a 2 ml syringe every 10 s, 30 s, 60 s, 120 s, and 300 s, then filter it through a filter and measure its absorbance using a UV-visible spectrophotometer; (4) The degradation test of ciprofloxacin and tetracycline is the same as above.

[0039] Application Example 2 Water Pollutant Degradation Experiment The hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial obtained in Comparative Example 1 is used to degrade water pollutants, and the specific steps are as follows: (1) Weigh 4 mg of hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterials into a 100 ml beaker, and then measure 40 ml of 10 ppm enrofloxacin solution and add it into the beaker; (2) Ultrasonicate the mixed solution in an ultrasonic machine for 10 seconds. Add a stirring bar to the beaker and place it on a magnetic stirring table. Use a pipette to add 80 μl of the prepared 1 mol / L PMS aqueous solution and start timing. (3) From the start of the timing, draw the solution in the beaker with a 2 ml syringe every 10 s, 30 s, 60 s, 120 s, and 300 s, then filter it through a filter and measure its absorbance using a UV-visible spectrophotometer; (4) The degradation test of ciprofloxacin and tetracycline is the same as above.

[0040] Application Example 3 Water Pollutant Degradation Experiment The spherical NiCo heterostructure nanomaterial obtained in Comparative Example 2 is used to degrade water pollutants, and the specific steps are as follows: (1) Weigh 4 mg of spherical NiCo heterostructure nanomaterials into a 100 ml beaker, and then measure 40 ml of 10 ppm enrofloxacin solution and add it into the beaker; (2) Ultrasonicate the mixed solution in an ultrasonic machine for 10 seconds. Add a stirring bar to the beaker and place it on a magnetic stirring table. Use a pipette to add 80 μl of the prepared 1 mol / L PMS aqueous solution and start timing. (3) From the start of the timing, draw the solution in the beaker with a 2 ml syringe every 10 s, 30 s, 60 s, 120 s, and 300 s, then filter it through a filter and measure its absorbance using a UV-visible spectrophotometer; (4) The degradation test of ciprofloxacin and tetracycline is the same as above.

[0041] Figure 6 This is a schematic diagram of the degradation rate of enrofloxacin in the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen that the degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial is greater than that of the other prepared materials, and the degradation degree can reach 95% in 5 minutes. Figure 7 This is a schematic diagram of the ciprofloxacin degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3DNiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen that the degradation rate of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial is greater than that of the other prepared materials, and the degradation degree can reach 95% in 5 minutes. Figure 8This is a schematic diagram of the tetracycline degradation rate of the hollow sea urchin-shaped 1D / 3DNiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the spherical NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen that the degradation rate of the hollow sea urchin-shaped 1D / 3DNiCuCo heterostructure nanomaterial is greater than that of the other prepared materials, and the degradation degree can reach 95% in 5 minutes. Fig. 9 This is a schematic diagram of the cyclic degradation rate of enrofloxacin by the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention. It can be seen that the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial can still have a degradation degree of more than 80% in 20 minutes after cyclic degradation of enrofloxacin 4 times, indicating that it has good degradation stability. Fig.10 These are the N2 adsorption-desorption curves of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the thorny ball-shaped NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen from the figure that the specific surface area of ​​the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial is much larger than that of the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial and the thorny ball-shaped NiCo heterostructure nanomaterial, which exposes more active sites. Fig.11 It is the oxygen vacancy curve of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial prepared in Example 1 of the present invention, the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial prepared in Comparative Example 1, and the thorny ball-shaped NiCo heterostructure nanomaterial prepared in Comparative Example 2. It can be seen from the figure that the oxygen vacancies of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial are much increased compared with the oxygen vacancies of the hollow sea urchin-shaped 1D / 3D NiCu heterostructure nanomaterial and the thorny ball-shaped NiCo heterostructure nanomaterial, and the oxygen vacancy defects also provide more active sites. Fig.12 This is a schematic diagram of the degradation rate of enrofloxacin by the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterials prepared in Example 1 of the present invention and nanomaterials synthesized from other transition metals. It can be seen that the nanomaterials doped with metal Co have better degradation effects than the nanomaterials doped with Zn and Mn.

[0042] Those skilled in the art will easily understand that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial, characterized by: The following steps are involved: (1) dissolving a divalent nickel salt, a divalent copper salt, a divalent cobalt salt and urea in ultrapure water to obtain a mixed solution, and uniformly dispersing the solution by ultrasonication; (2) The mixed solution obtained in step (1) was transferred to a polytetrafluoroethylene reactor and placed in an oven for hydrothermal reaction; (3) The solution obtained in step (2) is centrifuged and freeze-dried to obtain a hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial.

2. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: In step (1), the divalent nickel salt is nickel chloride hexahydrate, the divalent copper salt is copper chloride dihydrate, and the divalent cobalt salt is cobalt chloride hexahydrate.

3. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: The molar ratio of the divalent nickel salt, divalent copper salt, divalent cobalt salt and urea in step (1) is 8.5 mmol: 1 mmol: 1.5 mmol: 60 mmol; and the volume of ultrapure water is 50 mL.

4. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: The ultrasonic time in step (1) is 15 minutes.

5. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 120° C., and the time of the hydrothermal reaction is 24 h.

6. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: The centrifugal speed in step (3) is 8000 rpm, the centrifugal time is 3 min, and the centrifugation is performed twice alternately with ethanol and deionized water.

7. The method for preparing the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial according to claim 1, characterized in that: The freeze-drying step in step (3) is to place the product in a vacuum freeze dryer for 12 hours.

8. A hollow sea urchin-like 1D / 3D NiCuCo heterostructure nanomaterial prepared by the method according to any one of claims 1 to 7.

9. Use of the hollow sea urchin-shaped 1D / 3D NiCuCo heterostructure nanomaterial as claimed in claim 8 in efficient water treatment.

Citation Information

Patent Citations

  • Copper-based ternary mixed metal oxide hollow nano-material, preparation method and application thereof

    CN106807380A

  • Preparation method of nickel-copper cobaltate nanoparticles, and applications of nickel-copper cobaltate nanoparticles in catalysis of hydrolysis of ammonia borane to produce hydrogen

    CN111137927A

  • Water treatment method for activation of persulfate through zero-valent metal reinforced copper

    CN112811557A

  • Preparation and application of chestnut-shaped hollow NiCu composite material

    CN115888718A

  • HYDROGENATING TREATMENT OF HEAVY HYDROCARBON OILS CONTAINING ASPHALTENES AND CATALYSTS FOR SAID TREATMENT.

    IT8026251A0